Preferensi Konsumen Terhadap Pembelian Produk Pupuk Organik Kulit Pisang - Zuhri, Farhan; Priyanto, Moh. Wahyudi (LP3M Universitas Putra Bangsa, 2024)
Currently, the Ministry of Agriculture has made a decision to reduce the allocation of subsidized fertilizers, thus opening up opportunities for fertilizer producers, especially organic fertilizers that are proven to be more environmentally friendly. One of the organic fertilizer products that is classified as in the developing stage is banana peel organic fertilizer. This study aims to determine the characteristics and preferences of consumers towards the purchase of banana peel organic fertilizer products. The analysis methods used are qualitative descriptive analysis and conjoint analysis through the distribution of questionnaires online. The results of the data analysis in this study indicate that organic fertilizer consumers are dominated by women; the average age is 26–55 years; the last level of education is at the high school level; and they work as housewives with middle and lower middle incomes. The order of attributes in banana peel organic fertilizer products that are considered most important to consumers are price, texture, information, accessibility, and legality. The advice given is to use the minimum cost method to minimize production prices. Information can be carried out using the pick-up method because consumers like information obtained directly, and maintaining a smooth fertilizer texture.